Fish cognition and behavior (Blackwell Pub., 2006)
In this fascinating book an international team of experts have been brought together to explore all major areas of fish learning, including foraging skills, predator recognition, social organisation and learning, welfare and pain. Fish Cognition and Behavior is an important contribution to all fish biologists and ethologists and contains much information of commercial importance for fisheries managers and aquaculture personnel.